CryoSat-2 Antarctic Snow Freeboard Estimates - Fons, Steven; Kurtz, Nathan; Bagnardi, Marco; Petty, Alek; Tilling, Rachel (Zenodo, 2021)
Along-track and gridded estimates of Antarctic snow freeboard derived from CryoSat-2 Baseline-D SAR and SARIn data from October 2018 through October 2020. Data are generated using a physical retracker and waveform-fitting method. Files include: CS2SFb_ant_25km_YYYYMM.nc: Monthly mean snow freeboard values gridded on the NSIDC 25km polar stereographic grid. Each file represents 1 month of data between October 2018 and October 2020 (25 files). CS2SFb_ant_alongtrack_YYYYMMDD.nc: Along-track estimates of Cryosat-2 snow-freeboard for two profiles with near-coincident overlaps with ICESat-2. Files come from 20181027 and 20190902.